Endourologic Procedures for Benign Prostatic Hyperplasia: Review of Indications and Outcomes - Kacker, Ravi; Williams, Stephen B (Urology Journal, 2011)
Purpose: To discern the positive and negative attributes of the various treatment modalities for benign prostatic hyperplasia. Materials and Methods: A comprehensive literature review is presented for endoscopic treatment of the bladder outlet obstruction with an emphasis on current randomized controlled trials available comparing these treatment modalities. Results: Transurethral resection of the prostate remains the gold standard when assessing alternative treatment options available for benign prostatic hyperplasia. Holmium laser enucleation of the prostate demonstrates equivalent efficacy with a more favorable risk profile. Photoselective vaporization, transurethral needle ablation, and transurethral microwave therapy have demonstrated safety and short-term efficacy; however, data on long-term efficacy are currently lacking. Conclusion: The current endoscopic methods may offer favorable safety and efficacy for the treatment of the bladder outlet obstruction. However, further research is needed to establish long-term efficacy for many of the currently available treatment options.